Green innovation in a balance-of-payments constraint growth model for developing economies with capital inflows: The Latin America scenario - Flauzino de Souza, Leonardo; Santos de Amorim, Wellington (PSL Quarterly Review, 2024)
The main purpose of the paper is to build a balance of payments constraint model with capital inflows, where green innovations are inducers of the structural change process. The main results indicate that green R&D can reduce the growth rate of natural resource use. On the other hand, green structural change will only occur if foreign direct investment has spillover effects on green R&D.